USING YOUTUBE MEDIA TO ENHANCE STUDENTS’ VOCABULARY MASTERY - Tazkia Nurul Ikhlasa; Suryadi Suryadi (PROJECT (Professional Journal of English Education), 2023)
The purpose of this research was to examine how students can benefit from using YouTube media to expand their vocabulary. Learning outcomes were compared between the experimental class and the control class using a quasi-experimental approach with a nonequivalent control group. The pre- and post-treatment group (PPG) was employed. At SMP Negeri 5 Kota Serang, where the pre- and post-design (PPG) methodology was implemented, the research population was comprised of 297 students in grade VIII, and the sample size was 80 from this group. A random sampling strategy was used for the sampling. T test was employed for examination of the data. Based on the data, the calculated T value was 7.313, and the associated sig value was 0.000<0.05. So, it was safe to say that students who used youtube media had a marked increase in their command of the English language. Future studies should focus more on how students use new media and technology in English classroom materials. Keywords:  Youtube Media; Students’ Vocabulary Mastery